Leadership Styles in Improving Employee Work Motivation in Islamic Banks in Indonesia a Systematic Literature Review - Asma Khodijah (Yayasan Mitra Peduli Indonesia, 2026)
Leadership style plays a crucial role in shaping employee work motivation, including in the Islamic banking sector. This study aims to identify and analyze leadership styles and their implications for employee work motivation. This study employed a qualitative method with a systematic literature review approach. This study employed a systematic literature review to examine previous studies on leadership and work motivation in the Islamic banking context. This study found that transformational and participatory leadership styles tend to have a more positive impact on employee work motivation than autocratic or laissez-faire leadership styles. Then, transformational leadership styles encourage employee commitment to the organization's vision and improve performance through inspiration and empowerment. Meanwhile, participatory styles involve employees in decision-making, enhancing a sense of belonging and intrinsic motivation. These research findings should concern managers in Islamic banks and prompt them to adopt a leadership approach that supports employee productivity, satisfaction, and well-being. They also emphasize the importance of adapting leadership styles to organizational characteristics and employee needs to create a more effective, conducive work environment.